2017
DOI: 10.1097/mbc.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and osteoporosis in hemophilic children

Abstract: The aim of this study is to investigate bone state and factors affecting it in children with hemophilia. This is a case-control study that included 37 children with hemophilia and 37 healthy controls. The patients were selected from the outpatient pediatric hematology clinic of Fayoum University Hospital, Egypt. Bone mineral density, serum vitamin D, parathormone, calcium, phosphorus, and calcium creatinine ratio levels were evaluated. Vitamin D level and bone mineral density were significantly lower in hemoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…In the current study, there was a significant negative correlation between 25(OH) vit D level and HJHS ( R = −.384) and ( P = .006) and a positive correlation between serum vitamin D level and DEXA z‐score ( R = .323) and ( P = .022). Similarly, Eldash et al found that vitamin D level is positively correlated with z‐score of DEXA scan and negatively correlated with J‐score in adult patients with severe haemophilia A. However, Wells et al found no correlation between 25(OH)D and BMD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the current study, there was a significant negative correlation between 25(OH) vit D level and HJHS ( R = −.384) and ( P = .006) and a positive correlation between serum vitamin D level and DEXA z‐score ( R = .323) and ( P = .022). Similarly, Eldash et al found that vitamin D level is positively correlated with z‐score of DEXA scan and negatively correlated with J‐score in adult patients with severe haemophilia A. However, Wells et al found no correlation between 25(OH)D and BMD.…”
Section: Discussionmentioning
confidence: 91%
“…Upon comparing the laboratory and radiological data of the haemophilia children and controls, there was a significantly lower serum level of vitamin D ( P < .001) and DEXA z‐score ( P < .001) in patients with severe haemophilia A than the control group. These results are in concordance with Eldash et al , who found that both vitamin D level and BMD were significantly lower in people with haemophilia than control group ( P < .001). Also, Wells et al showed that adults with severe haemophilia A had reduced bone mineral density compared to a control group.…”
Section: Discussionmentioning
confidence: 98%
“…11 Reduced levels of vitamin D were observed in children with haemophilia. 12 The Haemophilia Joint Health Score (HJHS) was developed to assess joint damage in children with haemophilia. For teenagers and young adults, it correlates strongly with the x-ray-derived Pettersson score (rho = 0.86) and its inter-observer reliability was rated to be excellent.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of matrix metalloproteinases, such as MMP‐2, have been shown to be present in osteoarthritis, and once these MMPs are fully activated, they may contribute to the destruction of cartilage 11 . Reduced levels of vitamin D were observed in children with haemophilia 12 . The Haemophilia Joint Health Score (HJHS) was developed to assess joint damage in children with haemophilia.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports show that patients with hemophilia have significantly lower vitamin D levels than healthy people, and vitamin D deficiency might result in poor bone density. [96][97][98]…”
Section: Other Possible Ways That Hemophilia Might Affect Bone Remodementioning
confidence: 99%